Study on bearing characteristics of super-long and super-large diameter pipe piles in silt foundation of alluvial plain of Yellow River - Zhang, Sifeng; Ren, Zhicheng; Zhang, Yingguang; Fan, Wei; Li, Chao; Liu, Chao; Wang, Yushuai (Frontiers in Earth Science, 2024)
In recent years, super-long and super-large diameter pipe piles have been gradually applied to the foundation in the Yellow River flood area. However, its bearing mechanism is not clear, especially the unclear bearing characteristics of the pile under the eccentric state, which limits its application and development. In this regard, this paper uses the method of combining field test and numerical simulation to analyze the bearing characteristics of super-long and super-large diameter pipe piles under different pile lengths, different pile diameters, different diameter-thickness ratios, and different offsets. Combined with the specific deviation form of the pipe pile, the calculation formula of the vertical ultimate bearing capacity of the super-long and super-long diameter pipe pile in the Yellow River flooding area under the influence of the construction effect is modified.The results show that when the length of the pipe pile changes, the vertical bearing capacity changes the most, and the vertical ultimate bearing capacity of the pipe pile increases linearly with the increase of the length of the pipe pile. When the wall thickness of the pipe pile increases, the vertical bearing capacity increases approximately linearly, but the reduction of the pile displacement decreases exponentially.The greater the deflection of the pipe pile, the smaller the vertical ultimate bearing capacity. When the deflection of the pipe pile is greater than 0.35 °, the vertical ultimate bearing capacity decreases rapidly with the increase of the deflection. On the basis of the traditional formula, considering the deviation form of the pipe pile, the reduction coefficient of the bearing capacity correction formula of the super-long and super-large diameter pipe pile is proposed, and the correction formula is compared with the field example. It is proved that the formula can accurately calculate the bearing capacity of the super-long and super-large diameter pipe pile.